2011
DOI: 10.1021/la201535x
|View full text |Cite
|
Sign up to set email alerts
|

Superlubricity Behavior with Phosphoric Acid–Water Network Induced by Rubbing

Abstract: In present work, a superlubricity phenomenon of phosphoric acid (H(3)PO(4)) was found under ambient conditions. An ultralow friction coefficient of about 0.004 between glass/Si(3)N(4) and sapphire/sapphire tribopairs was obtained under the lubrication of a phosphoric acid aqueous solution (pH 1.5) at high contact pressure (the maximum pressure can reach about 1.65 GPa) after a running-in period of about 600 s. The experimental results indicate that the superlow friction state was very stable for more than 3 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
164
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 37 publications
3
164
1
1
Order By: Relevance
“…At present, superlubricity materials include solid lubricants (diamond like carbon (DLC), molybdenum disulfide (MoS 2 ), etc.) [88][89][90] and liquid lubricants [91][92][93][94][95][96][97]. The solid lubricants have been studied in detail by molecular dynamics simulations and experimental investigations.…”
Section: Superlubricity Owing To Tribochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…At present, superlubricity materials include solid lubricants (diamond like carbon (DLC), molybdenum disulfide (MoS 2 ), etc.) [88][89][90] and liquid lubricants [91][92][93][94][95][96][97]. The solid lubricants have been studied in detail by molecular dynamics simulations and experimental investigations.…”
Section: Superlubricity Owing To Tribochemistrymentioning
confidence: 99%
“…However, the investigation on liquid lubricants for superlubricity is still at the early stage. Li et al found the novel superlubricity phenomenon of phosphoric acid (H 3 PO 4 ) under ambient conditions [91,98]. An ultralow friction coefficient of about 0.004 between glass/Si 3 N 4 and sapphire/sapphire tribopairs was obtained under the lubrication of a phosphoric acid aqueous solution (pH 1.5) at high contact pressure (the maximum pressure can reach about 1.65 GPa), after a running-in period of about 600 s. The tribological results showed that the whole friction process could be divided into three stages according to the evolution of friction coefficient with time.…”
Section: Superlubricity Owing To Tribochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…A solution of phosphoric acid was found to be unique, providing an extremely low friction coefficient that was less than 0.004 by Li et al [135], Ma et al [136] and Li et al [137,138], who achieved superlubricity with alcohols and acids solutions successively. They suggested that the superlubricity of acid and glycerol solutions resulted from a shear-induced hydrogen network structure in a nano-gap, as shown in Fig.…”
Section: Advances Of Tfl Studies In Liquid Superlubricitymentioning
confidence: 99%
“…Phosphoric acid solutions exhibit superlubricity effect as a lubricant [103] with a friction coefficient around 0.004 after a short running-in period (Fig. 22).…”
Section: Acid Solutionsmentioning
confidence: 99%